Semiotika Karapan Sapi dan Transformasi Simbolik Masyarakat Madura - Pambudi, Buyung (Jurnal Komunikasi Islam, 2015)
Madura society is synonymous with a rough character. This article discusses the transformation of the symbolic character of the Madurese through Karapan Sapi, known hard to be anti-violence. By using qualitative methods and through a semiotic approach, this study suggests that there has been a change in the character of the Madurese, which is shown through the change symbols in Karapan Sapi. It can be seen from the removal rekeng used as a symbol of violence in the cattle races, and replaced with a regular whip made of materials not sharp. Thus it is the initiative of the community leaders, traditional leaders, religious leaders, and the government to change the imple–mentation of cattle races, without violence.